1996
DOI: 10.1507/endocrj.43.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2 Years' Treatment of Osteoporosis with 1 a-Hydroxy Vitamin D3 on Bone Mineral Density and Incidence of Fracture: A Placebo-Controlled, Double-Blind Prospective Study.

Abstract: Abstract.A two-year double-blind study monitored and evaluated the effects of 1a-hydroxy vitamin D3(1a(OH)D3) on the lumbar (L2.4BMD) and total body bone mineral densities (TBBMD) and occurrence of fracture in 113 female osteoporotic patients receiving 0.75 jig/day of 1a(OH)D3 (n=57) or a placebo (n=56) with calcium supplementation in both groups. L2~BMD increased 1.81% and 2.32% after one and 2 years in the 1a(OH)D3group, but decreased 1.89% (P<0.05) and 0.28% in the placebo group. A significant difference (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 21 publications
1
34
0
7
Order By: Relevance
“…Prior to data analysis, the bone density measurement data were examined for reliability by the Bone Mass Assessment Committee, generally according to the method reported previously [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to data analysis, the bone density measurement data were examined for reliability by the Bone Mass Assessment Committee, generally according to the method reported previously [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, several preparations such as active vitamin D3 analogues [4,5], calcitonin [6], vitamin K2 [7], ipriflavone [8], etidronate [9] and estrogen derivative [10] have been approved for the treatment of osteoporosis because these drugs increase the bone mass of patients with osteoporosis. Of these preparations, etidronate, a derivative of bisphosphonate, has been reported to be a potent inhibitor of bone resorption [11].…”
Section: Shirakimentioning
confidence: 99%
“…63,64,[117][118][119][120][121][122][123] These trials included those in which patients in both the intervention and control groups received calcium and/or vitamin D in comparable doses. Those studies in which vitamin D derivatives were compared with another active intervention are discussed later (page 36).…”
Section: Vitamin D Derivativesmentioning
confidence: 99%
“…64,118,120,123 In three studies, vertebral fracture was a secondary outcome measure 63,119,133 and in two, in which vertebral fracture was included as an outcome measure, there was no apparent differentiation between primary and secondary outcome measures. 117,121 Non-vertebral fractures were a secondary outcome measure in three studies, 63,122,123 and were mentioned in a further study that did not appear to differentiate between primary and secondary outcome measures. 121 In only five studies were effects on vertebral fractures reported as the numbers of patients in each arm sustaining fractures.…”
Section: Vitamin D Derivativesmentioning
confidence: 99%
See 1 more Smart Citation